2021
DOI: 10.11646/zootaxa.4963.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Disersus otongachi a new species of Larainae riffle beetles from Ecuador <br />(Coleoptera: Elmidae)

Abstract: We describe here a new species in the genus Disersus Sharp, 1882 from the Otongachi Reserve in Ecuador. Disersus otongachi sp.nov. is externally similar to other representatives of the genus, however, this species can be clearly distinguished for significantly longer antennae and the unique shape of the male genitalia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 539 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These differences are like previous studies [ 16 , 22 , 115 , 116 ], which found that genera in the Elmidae family differ regarding their ecological requirements. In this context, despite some relevant works that have been published on the taxonomy of the Ecuadorian Elmidae in the last few years [ 117 , 118 , 119 ], no work has been done about species distribution modelling of Elmidae. Further, to the best of our knowledge, just one SDM study using MaxEnt considered Elmidae in a southern Brazilian basin [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences are like previous studies [ 16 , 22 , 115 , 116 ], which found that genera in the Elmidae family differ regarding their ecological requirements. In this context, despite some relevant works that have been published on the taxonomy of the Ecuadorian Elmidae in the last few years [ 117 , 118 , 119 ], no work has been done about species distribution modelling of Elmidae. Further, to the best of our knowledge, just one SDM study using MaxEnt considered Elmidae in a southern Brazilian basin [ 60 ].…”
Section: Discussionmentioning
confidence: 99%